Growth of Pseudotypes of Vesicular Stomatitis Virus with N-Tropic Murine Leukemia Virus Coats in Cells Resistant to N-Tropic Viruses - Huang, Alice S. (1973)
Formation of pseudotypes between murine RNA tumor viruses and vesicular stomatitis virus (VSV) has been confirmed. Pseudotypes of VSV genomes coated by the surface envelope from an N-tropic tumor virus grew equally well in cells homozygous for either the Fv-1(n) or Fv-1(b) alleles. Therefore, the product of the Fv-1 locus, which restricts growth of murine RNA tumor viruses, must act on an intracellular aspect of tumor virus replication, a step after attachment and penetration.